2020
DOI: 10.5397/cise.2020.00185
|View full text |Cite
|
Sign up to set email alerts
|

Results of radial head resection after Mason type 3 or 4 fracture of the elbow

Abstract: Background: Resection of the radial head is a surgical indication for comminuted radial head fracture in which internal fixation is inaccessible. Some complications from the surgery can alter the function of the patient's elbow. The objective of this study was to assess functional outcome of the elbow after resection of the radial head. Methods: A retrospective longitudinal study was performed with patients who underwent radial head resection between 2008 and 2018. Elbow function was assessed by the Mayo Elbow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Clinical and radiological results from a retrospective review have documented good recovery in MEPS (from 79 to 100), DASH (from 4 to 15), and an acceptable elbow ROM (average 120°)following radial head resection [ 19 ]. Mebouinz et al [ 20 ] have demonstrated radial head resection can restore elbow functionality at a rate of 81%. However, due to the damaged radiocapitellar contact, RHR has an increased risk of complications such as instability of valgus or posterolateral rotation, decreased strength, and degenerative changes in elbow and wrist [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and radiological results from a retrospective review have documented good recovery in MEPS (from 79 to 100), DASH (from 4 to 15), and an acceptable elbow ROM (average 120°)following radial head resection [ 19 ]. Mebouinz et al [ 20 ] have demonstrated radial head resection can restore elbow functionality at a rate of 81%. However, due to the damaged radiocapitellar contact, RHR has an increased risk of complications such as instability of valgus or posterolateral rotation, decreased strength, and degenerative changes in elbow and wrist [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Formerly, radial head resection was a typical procedure treating unreconstructable radial head fractures [ 13 ]. However, it is avoided nowadays, because the radius can migrate proximally and cause distal radio-ulnar joint complaints and reduce elbow joint stability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the radial head is a key structure involved in maintaining the stability of the lateral side of the elbow joint and bears 20-30% of the valgus stability ( 30 ). When subjected to valgus stress, the radial head can reduce the tension stress on the inside of the elbow joint by acting on the fulcrum of the force arm ( 12 , 31 ). TTIE is often accompanied by damage to the lateral collateral ligament complex.…”
Section: Discussionmentioning
confidence: 99%